Implementation of Electronic Land Certificate Policy: A Case Study in Denpasar City - Anindyati, Farista Dewi; Hidayat, Rahmat; Akadun, Akadun (Sekolah Tinggi Pertanahan Nasional, 2025)
The electronic certificate policy was expected to be a step towards improving the quality of land services. However, the policy, initially formulated in the Regulation of the Minister of ATR/BPN No. 1 of 2021 concerning Electronic Certificates, was postponed due to content that raised public concerns, particularly regarding the regulation of analog certificate withdrawals. The Denpasar City Land Office became the first implementer of the electronic certificate policy in Indonesia following the enactment of Regulation No. 3 of the Minister of ATR/BPN in 2023. The purpose of this study was to analyze how the electronic land certificate policy was implemented at the Denpasar City Land Office using George C. Edward III's theory, which focuses on aspects of communication, resources, disposition, and organizational structure using qualitative research methods. Based on the research results, it was determined that the successful implementation of the electronic land certificate policy at the Denpasar City Land Office was inseparable from the commitment of the leadership and all staff, in addition to effective communication, adequate resources, and a positive attitude among implementers. However, it is necessary to update the Standard Operating Procedures to adapt to existing electronic land services.